Reinvindication of pre-hispanic agricultural technologies for a future food crisis: A scientometric study of the high fields based on citespace and VOSviewer - Oscanoa Gamarra, Luis (2025)
This study aimed to bibliometrically analyze the scientific production on pre-Hispanic agricultural technologies, highlighting their potential to address contemporary challenges related to food security and sustainability. To achieve this, 584 documents from SCOPUS (1932–2024) were examined using VOSviewer and CiteSpace, enabling the mapping of co-authorship networks, keywords, and institutional collaborations, as well as reviewing citation indicators, h-index, and gindex. The results indicate a substantial increase in publications since the 1980s, with accelerated growth from the 2000s onward. The United States leads in publication volume, followed by the United Kingdom, China, India, and France. Prominent among the research institutions are multidisciplinary centers specializing in archaeology, ecology, and biotechnology. Influential journals in the field include Journal of Archaeological Science, The Holocene, and Vegetation History and Archaeobotany. The keyword analysis underscores the significance of ancestral agricultural systems (raised fields, terraces, chinampas) and the integration of modern methodologies (genomics, remote sensing) to enhance their applicability in climate change scenarios. In conclusion, the growing attention to these technologies highlights their value as viable and sustainable alternatives, rooted in agroecological diversity, to strengthen food security and increase the resilience of modern agricultural systems.